Characterization of the complete chloroplast genome of Centranthera grandiflora Benth (Orobanchaceae), an important species of medicinal herb. Issue 6 (3rd June 2021) - Zheng, Lan-Ping; Li, Li-Juan
Abstract: Centranthera grandiflora is an important medicinal herb within Orobanchaceae. To date, however, genetic studies on this species remain poor. Here, we assembled the complete chloroplast genome of C. grandiflora . Results showed that the genome was 147 655 bp in length, consisting of large and small single copy regions of length 83 550 and 14 891 bp, respectively, separated by two inverted repeat regions of 24 607 bp. Furthermore, the genome contained 132 genes, including 84 protein-coding genes, 39 tRNA genes, and eight rRNA genes. Phylogenetic analysis showed that C. grandiflora is closely related to the species of Orobanchaceae. The complete chloroplast genome of C. grandiflora should help in the conservation of genetic resources and appropriate utilization of this medicinal herb in the future.